2020
DOI: 10.3390/ijms21134646
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 Knockdown Resensitizes 5-Fluorouracil-Resistant Pancreatic Cancer Cells by Suppressing HO-1 and ABCG2 Expression

Abstract: Chemoresistance is a leading cause of morbidity and mortality in patients with pancreatic cancer and remains an obstacle to successful treatment. The antioxidant transcription factor nuclear factor (erythroid-derived 2)-related factor 2 (NRF2), which plays important roles in tumor angiogenesis and invasiveness, is upregulated in pancreatic ductal adenocarcinoma (PDAC), where it correlates with poor survival. Here, we investigated the role of NRF2 in two 5-Fluourouracil-resistant (5-FUR) PDAC cell lines: BxPC-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Knockdown of EIF2AK1 led to increased protein translation and accumulation resulting to cell death after bortezomib exposure. Another study in pancreatic cancer cell lines that were resistant to 5-FU chemotherapy showed that these lines displayed stem cell and EMT markers expression and high activity of the proteasome master regulator NFE2L2[ 122 ]. Knockdown of NFE2L2 in this model sensitized cells to 5-FU.…”
Section: The Proteasome and Its Regulation In Emt And Stemness And Therapeutic Implications In Pancreatic Cancermentioning
confidence: 99%
“…Knockdown of EIF2AK1 led to increased protein translation and accumulation resulting to cell death after bortezomib exposure. Another study in pancreatic cancer cell lines that were resistant to 5-FU chemotherapy showed that these lines displayed stem cell and EMT markers expression and high activity of the proteasome master regulator NFE2L2[ 122 ]. Knockdown of NFE2L2 in this model sensitized cells to 5-FU.…”
Section: The Proteasome and Its Regulation In Emt And Stemness And Therapeutic Implications In Pancreatic Cancermentioning
confidence: 99%
“…Surgical resection is the only curative option; however, only 15% to 20% of patients have resectable tumors at initial diagnosis and most patients with locally advanced or metastatic PDAC require systemic chemotherapy. 2 Local ablative therapy including cryotherapy, irreversible electroporation, stereotactic body radiation therapy, and RFA might become potentially relevant in two major indications. One is palliation of cancer related symptoms and the other is local disease control.…”
Section: Pancreatic Ductal Adenocarcinomamentioning
confidence: 99%
“…In pancreatobiliary disease, endoscopic retrograde cholangiopancreatography (ERCP)-guided intraductal RFA has also been increasingly performed in malignant biliary tract obstruction. [2][3][4][5] However, the RFA for the pancreas is under investigation due to the increased risk of adverse events. Because the pancreas is a thermosensitive organ with more complex vascular systems, pancreatic neoplasms could infiltrate the bile duct or the duodenal wall, encase major vessels, or occlude the main pancreatic duct (MPD) by proximity.…”
Section: Introductionmentioning
confidence: 99%
“…Through received with surgical treatment or neoadjuvant/adjuvant chemotherapy, the prognosis of PaCa patients is far below the expectancy (Wang et al 2020b). Predominantly, resistance to chemotherapy is listed for the obstacle for treatment of PaCa patients (Kim et al 2020). Indicatively, cancer stem cells and epithelial-mesenchymal transition (EMT) are the involved actors to promote PaCa cell metastasis and drug resistance (Wang et al 2020c).…”
Section: Introductionmentioning
confidence: 99%